Focused Beam Antennas - Hoole, P.R.P. (Smart Antennas and Electromagnetic Signal Processing for Advanced Wireless Technology, 2020)
This chapter presents the most powerful antennas which allow for narrow, focused, and steerable antenna beams. This is primarily achieved by using two or more individual antenna elements and arranging them in different geometrical positions and controlling the amplitude and electronic phase angle of the signals received by the array antenna or being delivered to the array for transmission. Two-element array is analyzed to get the fundamentals of array antennas resolved, with the dipole wire antennas forming the elements of the array. Further, the N linear array antenna, where the antenna elements are placed in a straight line, is described as analyzed. Following this, the aperture antennas are discussed which produce narrow, directed single main beams. This includes the patch antenna and the horn antenna. These individual patch and horn antennas may be used in an array, instead of the dipole wire antenna, to obtain narrower steerable beams, as in wireless mobile systems and large dish antennas used for space research.